2005
DOI: 10.4314/njps.v19i1.32641
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Fresh And Thermoxidized Palm Oil Diets On Some Haematological Indices In The Rat

Abstract: Summary:The effects of fresh and thermoxidized palm oil diets on some haematalogical indices in the rat were investigated in albino rats (Wistar strain). The animals were divided into three groups namely, the first group fed on thermoxidized palm oil (TPO) diet, a second group fed on fresh palm oil (FPO) diet and a third fed on normal rat feed (control) only respectively for 14 weeks. Each of the palm oil diets contained 15% (w/w) thermoxidized or fresh palm oil. The packed cell volume (PCV) of the TPO group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
19
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 14 publications
9
19
1
1
Order By: Relevance
“…A related study by Adam et al [2008b] revealed that consumption of repeatedly heated soy Unauthenticated Download Date | 5/8/18 6:51 AM oil increased the serum parameters related to atherosclerosis in ovariectomized rats. In another study, it was suggested that chronic consumption of thermally-oxidized palm oil may cause anaemia and leukocytosis in rat [Mesembe et al, 2004]. This fi nding was further corroborated by Ani et al [2015a] who reported that thermally-oxidized palm and groundnut Symbol interpretation: -increased; -decreased; -no changes.…”
Section: Health Implications Of the Consumption Of Thermally-oxidizedmentioning
confidence: 64%
“…A related study by Adam et al [2008b] revealed that consumption of repeatedly heated soy Unauthenticated Download Date | 5/8/18 6:51 AM oil increased the serum parameters related to atherosclerosis in ovariectomized rats. In another study, it was suggested that chronic consumption of thermally-oxidized palm oil may cause anaemia and leukocytosis in rat [Mesembe et al, 2004]. This fi nding was further corroborated by Ani et al [2015a] who reported that thermally-oxidized palm and groundnut Symbol interpretation: -increased; -decreased; -no changes.…”
Section: Health Implications Of the Consumption Of Thermally-oxidizedmentioning
confidence: 64%
“…There was a significant increase in the hemoglobin concentration of the control group A and a slight increase/ negligible increase in group D. The hemoglobin concentration was significantly lower in the group that received 5ml/kg of 3% natron solution compared to the control group and other groups respectively. The decrease in the HB concentration may be a consequence of reduced uptake of iron by the damaged intestinal mucosa resulting in a reduced bioavailability of iron in the system [10] . The decrease in the HB concentration may also be attributed to the decreased storage of iron in the liver as a result of damage to the liver.…”
Section: Resultsmentioning
confidence: 99%
“…Produk degradasi karotenoid dapat berkontribusi pada reaksi radikal, tetapi efisiensinya tergantung pada spesies radikal dan struktur produk degradasi yang dihasilkan selama perlakuan temperature (Abbeddou, et al, 2013). Produk degradasi pigmen tomat ini memiliki kemungkinan senyawa- senyawa teroksidasi yang dapat menimbulkan efek radikal bebas dan risiko kesehatan (Mesembe OE, et al, 2004). Perlakuan temperatur yang lebih tinggi menyebabkan pigmen tomat yang didominasi oleh likopen mengalami penurunan konsentrasi.…”
Section: Hasil Dan Pembahasanunclassified